2020
DOI: 10.14569/ijacsa.2020.0110811
|View full text |Cite
|
Sign up to set email alerts
|

Design and Performance Analysis of Different Dielectric Substrate based Microstrip Patch Antenna for 5G Applications

Abstract: In this paper, a 3.5 GHz microstrip patch antenna using three different substrates materials with varying relative permittivity have been designed. However, the thickness of the substrates are slightly different from each other which is 1.6 mm for FR-4, 1.575 mm for RT-5880 and 1.58 mm for TLC-30 have been chosen to carry out this work. The three substrates materials are FR-4 (Design-1), RT-5880 (Design-2), and TLC-30 (Design-3) with the relative permittivity of 4.3, 2.2, and 3, respectively. The antennas' per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 6 publications
0
8
0
1
Order By: Relevance
“…The UCAs comprise identical microstrip patch antennas, which are uniformly placed in a circle on an FR-4 substrate with a thickness of 1.6 mm and a dielectric constant of 4.3. Microstrip patch antennas mainly comprise a radiating layer, substrate, and ground plane [16,17]. The substrate itself is located on a ground plane.…”
Section: Individual Patch Designmentioning
confidence: 99%
“…The UCAs comprise identical microstrip patch antennas, which are uniformly placed in a circle on an FR-4 substrate with a thickness of 1.6 mm and a dielectric constant of 4.3. Microstrip patch antennas mainly comprise a radiating layer, substrate, and ground plane [16,17]. The substrate itself is located on a ground plane.…”
Section: Individual Patch Designmentioning
confidence: 99%
“…Performance in terms of reflection coefficient, voltage standing wave ratio, bandwidth, gain, and efficiency are evaluated using CST Microwave Studio. For the next generation of 5G devices, antenna geometry to construct a compact size dual bands patch antenna is provided in [11]. Dual bands of 10.15 and 28 GHz for the 5G mobile communications are considered with directional radiation patterns.…”
Section: Literature Surveymentioning
confidence: 99%
“…The researchers showed how 5G communication would solve this problem using millimetre wave frequencies. Ramli et al [13] showed the benefits and demerits of 5G communication, along with the industry standards for certain countries. The paper reported how patch antennas are the best way to address these problems due to their design benefits and low cost.…”
Section: -Literature Reviewmentioning
confidence: 99%